2008
DOI: 10.1021/ja805900e
|View full text |Cite
|
Sign up to set email alerts
|

A Supramolecularly-Caged Ionic Iridium(III) Complex Yielding Bright and Very Stable Solid-State Light-Emitting Electrochemical Cells

Abstract: A new iridium(III) complex showing intramolecular interligand pi-stacking has been synthesized and used to improve the stability of single-component, solid-state light-emitting electrochemical cell (LEC) devices. The pi-stacking results in the formation of a very stable supramolecularly caged complex. LECs using this complex show extraordinary stabilities (estimated lifetime of 600 h) and luminance values (average luminance of 230 cd m-2) indicating the path toward stable ionic complexes for use in LECs reachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(108 citation statements)
references
References 21 publications
5
100
0
3
Order By: Relevance
“…The same group also showed that LECs with lifetimes of thousands of hours are obtained when using intramolecularly caged iridium(III) complexes ( Figure 25 and Table 2). [99,102,168,176] The cage formation effect occurs through an intramolecular p-p interaction between a pendant phenyl group attached to the N^N bpy ligand and the phenyl of the C^N cyclometalating ppy moiety. Complex 31 ( Figure 25) keeps its rigid cage conformation in the ground and excited states acquiring high stability against reactions with water.…”
Section: Light-emitting Electrochemical Cellsmentioning
confidence: 99%
“…The same group also showed that LECs with lifetimes of thousands of hours are obtained when using intramolecularly caged iridium(III) complexes ( Figure 25 and Table 2). [99,102,168,176] The cage formation effect occurs through an intramolecular p-p interaction between a pendant phenyl group attached to the N^N bpy ligand and the phenyl of the C^N cyclometalating ppy moiety. Complex 31 ( Figure 25) keeps its rigid cage conformation in the ground and excited states acquiring high stability against reactions with water.…”
Section: Light-emitting Electrochemical Cellsmentioning
confidence: 99%
“…The methyl substituents in complex 4 embrace the complex core as shown in Figure 1 b, which should reduce the possibility for nucleophilic attack, as we have observed for complexes containing phenyl substituents at the 6-and 6'-positions of the diimine ligand. [18][19][20][21][22] …”
Section: Synthesis and Structural Characterizationmentioning
confidence: 99%
“…High stability LECs have been obtained employing a specifi c type of iTMCs, in which an intracation π -π stacking between the ligands occurs. [18][19][20][21][22] Although very stable, these complexes showed a decrease in the photoluminescence quantum yields, thereby limiting the maximum device efficiencies that can be obtained. It is widely accepted that one of the degradation pathways of LECs is the breakdown of the Ir-iTMCs, most likely by nucleophilic attack analogous to the established pathway in ruthenium-based iTMCs.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13] One device that exploits this opportunity in an attractive manner is the light-emitting electrochemical cell (LEC). [14][15][16][17][18][19][20][21][22] The nominal difference between an LEC and an OLED is that the former contains mobile ions in the active material. [23][24][25][26][27][28][29][30] These ions rearrange during operation, which in turn allows for a range of attractive device properties, including low-voltage operation with thick active layers and stable electrode materials.…”
mentioning
confidence: 99%